Effects of Apolipoprotein E Polymorphism on Cerebral Oxygen Saturation After Traumatic Brain Injury - Wu, Zhimin; Xiong, Senjie; Sun, Xiaochuan; Shi, Quanhong; Dan, Wei; Zhan, Yan; Xie, Yanfeng; Jiang, Li (Frontiers in Neurology, 2020)
Objective: To investigate the effects of the apolipoprotein E gene (APOE) on the cerebral oxygen saturation of patients after traumatic brain injury (TBI). Methods: Clinical data of 114 patients with TBI and 54 normal people were collected. The APOE genotypes of all subjects were determined by quantitative fluorescent polymerase chain reaction (QF-PCR). The regional cerebral oxygen saturation (rScO2) of TBI patients and normal people were monitored by near-infrared spectroscopy (NIRS). Results: The mean rScO2 of patients was (55.06 ± 7.60)% in the early stage of TBI, which was significantly lower than that of normal people (67.21 ± 7.80)% (P < 0.05). Single-factor and multifactor logistic regression analyses showed APOEε4 was an independent risk factor that caused the early decline of rScO2 in TBI patients. Furthermore, in the TBI group, the rScO2 of APOEε4 carriers (52.23 ± 8.02)% was significantly lower than that of non-ε4 carriers (60.33 ± 7.12)% (P < 0.05). But in the normal group, no significant differences in rScO2 were found between APOEε4 carriers and non-carriers. Conclusion: The rScO2 may be significantly decreased after TBI, and APOEε4 may be a risk factor for decreased rScO2 in the early stage of TBI.